Cover Picture: Quantification of Active Sites and Elucidation of the Reaction Mechanism of the Electrochemical Nitrogen Reduction Reaction on Vanadium Nitride (Angew. Chem. Int. Ed. 39/2019). Issue 39 (23rd August 2019) - Yang, Xuan; Kattel, Shyam; Nash, Jared; Chang, Xiaoxia; Lee, Ji Hoon; Yan, Yushan; Chen, Jingguang G.; Xu, Bingjun
Abstract : The distinct isotopic identities of the incoming N2 and the surface N sites on an oxygen‐modified vanadium nitride catalyst enable the differentiation and quantification of active catalytic sites. In their Communication onpage 13768 ff., Y. Yan, J. G. Chen, B. Xu, et al. report the use of 14 N/ 15 N isotopic exchange to determine the density of initial and steady state active sites on vanadium oxynitride in the electrochemical nitrogen reduction reaction.